2010
DOI: 10.1117/1.3463006
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared Raman spectroscopy to detect anti-Toxoplasma gondii antibody in blood sera of domestic cats: quantitative analysis based on partial least-squares multivariate statistics

Abstract: Abstract. Toxoplasmosis is an important zoonosis in public health because domestic cats are the main agents responsible for the transmission of this disease in Brazil. We investigate a method for diagnosing toxoplasmosis based on Raman spectroscopy. Dispersive nearinfrared Raman spectra are used to quantify anti-Toxoplasma gondii ͑IgG͒ antibodies in blood sera from domestic cats. An 830-nm laser is used for sample excitation, and a dispersive spectrometer is used to detect the Raman scattering. A serological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…[11][12][13][14] Using dispersive or FourierTransform Raman techniques in the near-infrared spectrum, there is no need for additional chemical steps for analysis (separation, dilution, or mixture of other reagents) and may prove superior to current methods of testing urine, 11,12 nondestructively. Biochemical assays based on Raman spectroscopy could be used for testing body fluids such as blood, blood components, and metabolites in the serum for doping control, 15 detecting antibodies in cat's serum, 16 and even monitoring heparin levels in blood during surgeries. 17 Optical techniques may become a future alternative or even replace existing laboratory methods.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Using dispersive or FourierTransform Raman techniques in the near-infrared spectrum, there is no need for additional chemical steps for analysis (separation, dilution, or mixture of other reagents) and may prove superior to current methods of testing urine, 11,12 nondestructively. Biochemical assays based on Raman spectroscopy could be used for testing body fluids such as blood, blood components, and metabolites in the serum for doping control, 15 detecting antibodies in cat's serum, 16 and even monitoring heparin levels in blood during surgeries. 17 Optical techniques may become a future alternative or even replace existing laboratory methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Raman spectroscopy could be used to detect and quantify anti-Toxoplasma gondii IgG antibodies in sera of cats [52] and to detect dengue antibody IgM antibodies in human sera [53]. The Raman spectra were also used to detect hepatitis (B and C) virus infection in sera [54,55] as well as dengue virus infection also in sera [56].…”
Section: Exploratory Analysismentioning
confidence: 99%
“…Previous studies showed that Raman spectroscopy could be used to detect and quantify anti-Toxoplasma gondii IgG antibodies in sera of cats [58], to detect IgM antibody in dengue infection in human sera [59], and to detect IgM and IgG in sera of COVID-19 positive patients aiming diagnosis [29]. The Raman spectra were also used to detect hepatitis (B and C) virus infection in sera [60,61] as well as dengue virus infection also in sera [62].…”
Section: Exploratory Analysismentioning
confidence: 99%